Retroviral and Lentiviral Vectors for the Induction of Immunological Tolerance - Inès Dufait; Therese Liechtenstein; Alessio Lanna; Christopher Bricogne; Roberta Laranga; Antonella Padella; Karine Breckpot; David Escors (Scientifica)
Retroviral and lentiviral vectors have proven to be particularly efficient systems to deliver genes of interest into target cells, either in vivo or in cell cultures. They have been used for some time for gene therapy and the development of gene vaccines. Recently retroviral and lentiviral vectors have been used to generate tolerogenic dendritic cells, key professional antigen presenting cells that regulate immune responses. Thus, three main approaches have been undertaken to induce immunological tolerance; delivery of potent immunosuppressive cytokines and other molecules, modification of intracellular signalling pathways in dendritic cells, and de-targeting transgene expression from dendritic cells using microRNA technology. In this review we briefly describe retroviral and lentiviral vector biology, and their application to induce immunological tolerance.